Congenital Hairy Polyp of the Palatopharyngeus Muscle. (18th June 2013) - Christianson, Brandon; Ulualp, Seckin O.; Koral, Korgun; Rakheja, Dinesh; Deskin, Ronald
Abstract : Purpose . To describe clinical, radiologic, and histological features of a congenital hairy polyp arising from the palatopharyngeus muscle in a neonate. Methods . Chart of a 2-day-old female referred to a tertiary care pediatric hospital for assessment of intraoral mass was reviewed. Results . The child was born at 32 weeks and an intraoral mass was noted. The patient was transferred to tertiary care children's hospital on day 2 of life. The child had increased work of breathing at presentation and required continuous positive airway pressure. Physical examination revealed a pedunculated mass which was protruding into the oropharynx from the nasopharynx. MRI of the lesion documented a discrete bilobed mass which filled the posterior nasopharynx. The mass abutted the uvula and soft palate; however, the mass did not appear to be arising from the soft palate. Intraoperative exam showed a mass arising from the right palatopharyngeus muscle in the superior pole region of the tonsil. Histologic examination showed ectodermal and mesodermal derivatives confirming congenital hairy polyp. At 8-month followup, the surgical site was healed with no evidence of recurrent lesion. Conclusions . Congenital hairy polyp, though uncommon, should be considered in the differential diagnosis of oropharyngeal mass in neonates.